Increasing Public Understanding Of Early Detection Of Post-Covid-19 Economic Weakness - Rusiadi Rusiadi; Ade Novalina; Vivi Adianti (International Journal of Economics and Management Research, 2022)
This research aims to improve the Hero Village Community's understanding of the post-Covid-19 economic situation, especially the impact of the post-Covid-19 economic downturn. The people of Pahlawan Village still need to understand the causes of the post-Covid-19 economic downturn, the factors that influenced it, and the negative impacts of the post-Covid-19 economic downturn. In their lessons, there needs to be a discussion about how weakening can be detected early. Therefore, this service is carried out to understand the Hero Village Community about early detection and the models used to detect weakening such as rising prices and falling people's purchasing power. The results of the service prove that after being given an understanding of the post-COVID-19 economic outlook, people will take into account consumption, both household consumption and fuel consumption, for purchasing ship oil.